I am so lost and confused
![I am so lost and confused class=](https://us-static.z-dn.net/files/da2/f34a2da1c3ff226c09da94cf9d6f1877.png)
Answer:
The answer to your question is:
Step-by-step explanation:
f(x) = x² - 4 g(x) = 3x - 3
a. f(-2) = (-2)² - 4
= 4 - 4
= 0
b. f(-4) + g(-1) = (-4)² - 4 + 3(-1) - 3
= 16 - 4 - 3 - 3
= 16 - 10
= 6
c. 3f(x) + 2g( x) = 3(x² -4) + 2(3x - 3)
= 3x² -12 + 6x - 6
= 3x² + 6x - 18
d. f(g(4))
g(4) = 3(4) - 3
= 12 - 3
= 9
f(g(4)) = (9)² - 4
= 81 -4
= 77
e) f(4) = (4)² - 4
= 16 - 4
= 12
g(f(4)) = 3(12) - 3
= 36 - 3
= 33